Metformin with everolimus and octreotide in pancreatic neuroendocrine tumor patients with diabetes. (May 2016) - Pusceddu, Sara; Buzzoni, Roberto; Vernieri, Claudio; Concas, Laura; Marceglia, Sara; Giacomelli, Luca; Milione, Massimo; Leuzzi, Livia; Femia, Daniela; Formisano, Barbara; Mazzaferro, Vincenzo; de Braud, Filippo
A bidirectional relationship seems to exist between diabetes mellitus and development of pancreatic tumors. Metformin, the most widely used drug in the treatment of Type 2 diabetes mellitus, has recently emerged as a potentially active agent in cancer chemoprevention and treatment. In this article, we discuss the potential correlation between glycemic status, administration of antiglycemic treatments, such as metformin or insulin, and prognosis of pancreatic neuroendocrine tumors patients treated with everolimus and octreotide, on the basis of existing evidence and our experience.